Numerical modeling of heat transferin a flow around a cylinder using staggered grid method. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Manajemen Pelayanan Kesehatan, Fak. Kedokteran UGM, 2001)
Two dimensional numerical modeling of heat transfer in an incompressible fluid flow around a heated cylinder had been conducted. Discretisation using a staggered mesh was employed. The algorithm for integrating the Navier-Stokes equations was constructed in two stages, a combination of a direct and iteration methods. In order to keep the simplicity of the code development, the employment of body-fitted coordinate technique was avoided. Simple interpolation model was used to match the cylinder geometry. Solutions for heat transfer in a flow around a cylinder at various Reynolds and Peclet numbers were presented. It was found that validation to the transition to turbulence was quite satisfactory. The overall results gave reasonable flow and temperature distributions capable of showing the physics of fluid dynamics and its heat transfer mechanism. This method could be developed further to explore forced convection heat transfer in heat exchangers, boiler tubes, condenser and inside nuclear reactor vessels.